FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN TERHADAP KEPUTUSAN PEMBELIAN PADA COFFEE SHOP DI KAWASAN DENPASAR - Muhammad Fadhil Ikhsan; I Made Bayu Wisnawa; Ni Nyoman Rusmiati (Journal of Applied Management Studies, 2023)
This research aims to determine: i) the factor that determines tourists buying at coffee shop in the Denpasar area, and ii) the dominant factor that determine tourists decide to buy at coffee shop. The analytical tool used in solving this problem is factor analysis using the SPSS (Statistics Package of Social Science) 24.0 version for windows software program. The results of the research show that: i) the factor that determines tourists buy at coffee shop in the Denpasar area which include: Main factor (coffee shop facilities, name/brand, product price and building design) this factor is the dominant factor that determines tourists buy at coffee shop in the Denpasar area, Supporting Factor (strategic location, encouragement of local people, personal income and lifestyle), Convenience Factor (payment system, cleanliness of the coffee shop and parking facilities), Motivational Factor (discounted prices and expectations of satisfaction), Trust Factor (labor and promotional media), and ii) the dominant factor that determines tourists buy coffee shops in the Denpasar area is the Main Factor, this factor is formed by the variant of coffee shop facilities, name/brand, product price and building design